2018
DOI: 10.2144/000114629
|View full text |Cite
|
Sign up to set email alerts
|

A Gas Trapping Method for High-Throughput Metabolic Experiments

Abstract: Research into cellular metabolism has become more high-throughput, with typical cell-culture experiments being performed in multiwell plates (microplates). This format presents a challenge when trying to collect gaseous products, such as carbon dioxide (CO2), which requires a sealed environment and a vessel separate from the biological sample. To address this limitation, we developed a gas trapping protocol using perforated plastic lids in sealed cell-culture multiwell plates. We used this trap design to measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…For glucose oxidation experiments, cells were assayed as described previously (Krycer et al, 2018). Briefly, immediately upon addition of radiolabelled media and insulin (100 nM) treatment, gas-traps containing NaOH were installed and plates were sealed.…”
Section: Radiolabelling Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…For glucose oxidation experiments, cells were assayed as described previously (Krycer et al, 2018). Briefly, immediately upon addition of radiolabelled media and insulin (100 nM) treatment, gas-traps containing NaOH were installed and plates were sealed.…”
Section: Radiolabelling Experimentsmentioning
confidence: 99%
“…For lipogenesis experiments, cells were assayed as described previously (Krycer et al, 2018). Following incubation with radiolabelled medium, cells were washed thrice with ice-cold PBS and plates were frozen dry at -30 °C.…”
Section: Radiolabelling Experimentsmentioning
confidence: 99%
“…Since insulin potently promotes glucose uptake into adipocytes, we considered the role of glucose utilisation in adipose insulin resistance. We have previously observed that insulin stimulates glucose oxidation (13), glucose-fuelled TCA cycle flux (Quek et al, under review), and respiration (14) in adipocytes. Thus, we hypothesised that insulin stimulates respiration and subsequent mitoROS production in a glucose-dependent manner, with insulin resistance stemming from glucose oversupply.…”
Section: )mentioning
confidence: 99%
“…To achieve this, we modified a gas-trapping method that we previously established for cell culture models [10]. This involved culturing cells in sealed multi-well plates, where CO 2 was collected in a NaOH solution in a gas trap.…”
mentioning
confidence: 99%
“…It enables precise control over key experimental conditions such as diet and time, and is nondestructive, thus being amenable to time-course experiments and able to be coupled to the measurement of other parameters. Furthermore, we have previously shown that this assay format can detect the oxidation of radiolabeled palmitate in cell culture [10]; the oxidation of other substrates (e.g., fatty acids, amino acids) could similarly be studied in flies. This assay ultimately provides a useful tool for merging fly genetics with radioactive tracer metabolic studies to understand the response to macronutrients on an organismal level.…”
mentioning
confidence: 99%